+0  
 
0
167
2
avatar

2x2+5x-12

Guest Apr 17, 2017
Sort: 

2+0 Answers

 #1
avatar+6810 
0

2x+ 5x - 12

= 2 (x2 + 5x/2 - 6)

= 2 (x2 + 5x/2 + 25/8 - 73/8)

= 2(x + 5/4)2 - 73/4

= (2x + 2.5)2 - 73/4

\((2x + \dfrac{5}{2}-\dfrac{1}{2}\sqrt{73})(2x+\dfrac{5}{2}+\dfrac{1}{2}\sqrt{73})\)

MaxWong  Apr 18, 2017
 #2
avatar+6810 
0

Whoops what am I doing

I should do:

\(2x^2 + 5x - 12 = 0\\ x = \dfrac{-5 \pm \sqrt{5^2-4(2)(-12)}}{2(2)}\\ \;\;=\dfrac{-5\pm 11}{4}\\ x = \dfrac{3}{2}\text{ OR }-4\\ \therefore 2x^2 + 5x - 12 = (2x - 3)(x + 4)\)

MaxWong  Apr 18, 2017

15 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details